To Punish or to Forgive?: Responding to Dirty Hands in Politics. Issue 160 (1st September 2019) - Roadevin, Cristina
Abstract : How should citizens respond to dirty-hands acts? This issue has been neglected in the theoretical literature, which has focused on the dilemma facing the politician and not on the appropriate responses of citizens. Nevertheless, dirty-hands scenarios pose a serious dilemma for the democratic citizens as well: we cannot simply condone the dirtyhanded act but should instead express our moral condemnation and disapproval. One way of doing this is through blame and punishment. However, this proposal is unsatisfactory, as dirty-hands agents commit wrongdoing through no fault of their own. I argue that we ought to make conceptual space for an idea of no-fault responsibility – and a corresponding notion of no-fault forgiveness – according to which we can hold agents to obligations without blaming them.